(untitled) (Journal of Engineering, 2011)
Used vegetable oil was introduced to transesterfication reaction to produce Biodiesel fuel suitable for diesel engines. Method of production was consisted of filtration, transesterfication, separation and washing. Transesterfication was studied extensively with different operating conditions, temperature range (35-80oC), catalyst concentration (0.5-2 wt. % based on oil), mixing time (30-120 min.) with constant oil/methanol weight ratio 5:1 and mixing speed 1300 rpm. The concentration of Fatty acid methyl esters (Biodiesel) was determined for the transesterficated oil samples, besides of some important physical properties such as specific gravity, viscosity, pour point and flash point. The behavior of methyl esters production and the physical properties of Biodiesel were studied with the different operating conditions. The results show that increasing methyl esters concentration with increasing temperature and catalyst concentration and the transesterfication is a second order reaction The research aiming to recycle spent cooking oils to prevent pollution of soil and water, and converting them to Biodiesel fuel with low emissions